Learning Through Reflective Writing: A Teaching Strategy - Young, Kristen L. (Evidence Based Library and Information Practice, 2010)
Objective – To explore student thought on both reflection and reflective writing as a process, and to analyze the writing by the application of clearly defined and identifiable outcomes. Design – Mixed method approach consisting of a qualitative analysis of 116 written reflections from master’s level students as well as a quantitative statistical analysis. Setting –The University of Sheffield masters-level librarianship program’s course INF6005, “Management for LIS.” Subjects – Of the 31 students registered the course during the 2007-2008 academic year, 22 (71%), allowed their reflections to be used for the purposes of research. Of these, 7 students identified themselves as male, and 15 were female. All students included were over 21 years of age and had previous library experience, with varying degrees of management experience in supervisory roles. Not all supervisory experience was gathered within the library domain. Methods –A total of 116 reflective journal entries were submitted by the participating students during the eight month period from October 2008 to May 2009. In order to identify themes, qualitative analysis was applied to the reflective writing responses. Descriptive statistics were also applied to test the hypothesis, illustrate the relationships between reflective writing and outcomes, and locate identifiable outcomes. Main Results – Practising reflection demonstrated benefits for individuals and groups both in and outside of the workplace. On the whole, individuals gained the most from reflection and saw it in the most positive light when it was practised as a daily activity. Quantitatively, when students began to master the practice of reflection, they demonstrated an increase in their ability to learn and an overall improvement of self-development and critical thinking skills, and gained a defined awareness of personal mental function. When decision making became easier, students understood they had begun to master the art of reflective practice and analytical reflective writing. Qualitatively, when the students’ reflections were assessed, ten different themes emerged: (1) Nature of reflection (2) Reflection seen as useful in providing support for a career and professional development (3) Reflective writing – benefits (4) Reflective writing – potential in future employment and workplace (5) Encouraging others to use reflective practice (6) Reflecting positively (7) Reflection applicable to both individuals and groups (8) Reflection in support of personal awareness (9) Exploration of different methods of reflection (10) Difficulties in focusing enough to be able to reflect deeply Conclusion – Reflection is a skill that can be practised and developed. Initially, not all students enrolled in the class and participating in the study knew what reflective writing was or what it entailed. Students were given support to educate them in this area. Support included academic reading, lectures, reflective writing workshops and an overall opportunity to develop their skills further. Reflective writing was demonstrated to have a very positive relationship with several key outcomes. The areas impacted include academic learning, self-development, and critical review, with key outcomes including an increased awareness of personal mental function and increased support for decision making, as well as empowerment and emancipation. The clearest benefit was represented when students wrote about their analytical reflections.